Proceedings of the 3rd International Symposium of Information and Internet Technology (SYMINTECH 2018) - Othman, Mohd Azlishah; Abd Aziz, Mohamad Zoinol Abidin; Md Saat, Mohd Shakir; Misran, Mohamad Harris (Lecture Notes in Electrical Engineering,, 2019)
This book gathers the proceedings of a symposium on the role of Internet technologies and how they can transform and improve people's lives. The Internet is essentially a massive database where all types of information can be shared and transmitted. This can be done passively in the form of non-interactive websites and blogs; or it can be done actively in the form of file sharing and document up- and downloading. Thanks to these technologies, a wealth of information is now available to anyone who can access the Internet. Moreover, Internet technologies are constantly improving: growing faster, offering more diverse information, and supporting processes that would have been impossible in the past. As a result, they have changed, and will continue to change, the way that the world does business and how people interact in their day-to-day lives. In conclusion, the symposium and these proceedings provide a valuable opportunity for leading researchers, engineers and professionals around the globe to discuss the latest advances that are helping the world move forward. They also facilitate the exchange of new ideas in the fields of communication technology to create a dialogue between these groups concerning the latest innovations, trends and concerns, practical challenges and potential solutions in the field of Internet technologies. .